ESTIMATION OF HETEROSIS FOR YIELD AND YIELD CONTRUBUTING CHARACTERS IN SUNFLOWER (HELIANTHUS ANNUUS L.) - S. V. YAMGAR; M. K, GHODAKE; R. D. MALI (The Bioscan, 2015)
The experiment consisting of four cytoplasmic male sterile lines and seven restorers were crossed in line x tester fashion to estimate the heterosis for seed yield and yield contributing trait in sunflower resulting their 28 crosses were evaluated in two replication of randomized block design over two commercial checks LSFH-171 and LSFH- 35. The morphological observations on 10 quantitative characters were recorded. The extend of heterosis in 28 hybrids over mid parent (MP) ranging from 33.33 to 148.00 better parents (BP) ranged from 3.13 to 121.43 and standard heterosis over on check LSFH-35 ranged from -8.33 to 61.11 other check LSFH-171 showed heterosis ranged from-17.50 to 55.00 for seed yield while extend of heterosis for oil content in hybrids over mid parent (MP) ranging from -11.49 to 16.67.00 better parents (BP) ranged from -18.52 to 15.62 and standard heterosis estimated over one check LSFH-35 ranged from -16.98 to 2.12 and other check LSFH-171 ranged from -10.72 to 11.59 , The best crosses based on heterosis and sca effect per se performance were LSFH-221,LSFH-273,LSFH- 1218,LSFH-2421 and LSFH-2073 were identified as the best crosses combination for seed yield, oil content, yield characters. These better performing hybrids can be used for exploiting hybrid vigour and need to be evaluating stability parameter.